Financialisation and the microstructure of commodity markets: A qualitative investigation of trading strategies of financial investors and commercial traders - Christine Heumesser; Cornelia Staritz (Austrian Foundation for Development Research (ÖFSE), 2013)
The financialisation of commodity derivative markets, reflected in the increased presence of financial investors, and its effects on commodity prices and the fundamental roles of these markets, i.e. price discovery and price risk management for commercial traders, have been controversially discussed. This working paper provides an analysis of the microstructure of commodity derivative markets with a focus on the commodities coffee, cotton, wheat and aluminium. Two questions are in the center: firstly, how, in the context of financialisation, have the composition of traders and their trading strategies changed, and, secondly, how have the increasing presence and trading strategies of financial investors affected commercial traders, price discovery and hedging. The analysis builds on interviews with different types of market participants and relevant stakeholders. The paper finds that the increasing and often dominating role of financial investors has changed the microstructure of commodity derivative markets in terms of trading volumes and open interest positions, market participants, investment products and strategies, speed and complexity. The common classification of traders put forward by the US Commodity Trading Futures Commission seems to abstract too much from the reality in commodity markets given the multiple and interrelated roles of traders.Financial investors may have multiple roles, which include physical trading, and large commercial traders such as multinational trading houses typically pursue hedging and speculative trading strategies. Though financial investors are widely believed to increase the likelihood of excessive short term price fluctuations and commercial traders take into account their presence and strategies in their own trading behavior, they impact commercial traders in different ways. Large commercial traders seem not to be concerned about their increasing role or even perceive their presence as advantageous. But smaller commercial traders that do not have the resources and capacity to interact actively with derivative markets seem to find it more difficult to use markets for hedging given the increased complexity, speed and short-terminism and related higher risks and costs.
Keywords: 330; Rohstoffderivat; Spekulation; Institutioneller Investor; Rohstoffpreis; Marktmikrostruktur; Welt